(3efJNH Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3TeS GdOjf eJWHH cjdGfi (B( (3GdLjdGfi (B)s; (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s
(3ChdgG (B:s
(3GMeOc jG ef NQL GdNdGjb HdWa UfYg ef GdYOe Edi GdhLhO aEf gPg QSGdI efJNHI GfJNHJgG dfaSi jfHZi dcd ef jTJZd HUfGYI GdWH Cf jYQa cjajI hLhO UfGYI GdWH s
(3BNQgG (B:s
(3CHh GdaQL jMji Hf GdJdejP gh GdGLd GdMcje JeJ GdQSGdI GdefJNHI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B170 (3ef faS GdHYKIs
(3hQO GdYfhGf GdCUdi ai c X (B2/1185s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs